Three-dimensional navigation assisted pediatric foot and ankle surgery: Operative technique and safety profile - Ramez Sakkab, DPM; Hafsah Dean, DPM; Scott Shoemaker, MD; Ryan O'Shea, MD (Foot & Ankle Surgery: Techniques, Reports & Cases)
Computer-assisted surgery (CAS) is an innovative technology that provides surgeons with three-dimensional navigation (TDN) to optimize intraoperative visualization and guidance. Computer-assistance after intraoperative cone beam computed tomography is predominantly found in spinal surgery. The senior authors have applied the same principles and techniques to some lower extremity pathologies. The present study reviews lower extremity operative technique and safety profile with three-dimensional real-time navigation at a single institution. Technique for retrograde drilling of osteochondral lesions of the talus and pedal coalition resection(s) are presented. At our institution, thirty-five computer-assisted foot and ankle cases were identified from 2015 to 2022. Complications occurred in 8.6 % of cases (3/35). Over the past decade, the authors have employed a low dose protocol for intraoperative cone beam computed tomography. Doses from each tarsal coalition and talar osteochondral defect case were averaged, resulting in 1.48 and 1.14 milliGrays (mGy), respectively. Both surgeries demonstrate below 25 % of the annual background radiation dose (6.2 mGy). Further research is needed regarding three-dimensional navigation in foot and ankle surgery along with comparisons to radiation exposure via intraoperative fluoroscopy in similar cases.